Effect of thermocapillary action in the underfill encapsulation of multi-stack ball grid array. (November 2016) - Ng, Fei Chong; Abas, Aizat; Ishak, MHH; Abdullah, MZ; Aziz, Abdul
Abstract: Recent trend in electronic industries are demanding smaller chip packaging process along with increase in performance and reliability of the package. The introduction of Multi-stack Ball Grid Array (BGA) to enhance the performance of the conventional BGA flip chip has frequently encountered several hitches such as extended filling time and incomplete filling at the upper layer of the multi-stacks BGA. It has been found that the encapsulant lacks energy to flow at the upper layer due to lower hydrostatics pressure. In this paper, a straightforward solution by incorporating additional thermal energy in the encapsulant to increases its flow ability is introduced. This additional thermal energy at the upper layer produces a distinct temperature difference between the upper and lower layers, or simply thermal delta. This research attempts to demonstrate the effectiveness of thermal delta in solving the aforementioned flow problem during encapsulation process of multi-stacks BGA, by means of experiment and numerical simulation. The findings have shown that the experimental data compares well with the simulation results. It was also found that the implementation of thermal delta substantially reduces the filling time across the multi-stack packages. This study reveals the potential of thermocapillary-driven underfill encapsulation being widely adopted in future industrial encapsulation of multi-stacks BGA packaging. Highlights: Simulation and experimental study on the effect of thermal delta in accelerating the encapsulant flow in multi-stack BGA. Relatively similar experimental and simulation data typically at the 80% and 100% filling with relative error of about 10%. Thermal delta implementation on multi-stack BGA can accelerate the encapsulant flow across all BGA layers by up to 30%. Highest gauge pressure and velocity of the encapsulant is observed at the bottom layer followed by the middle and top layers.